Interaction of the prototypical α-ketoamide inhibitor with the SARS-CoV-2 main protease active site in silico: Molecular dynamic simulations highlight the stability of the ligand-protein complex. (August 2020) - Liang, Julia; Pitsillou, Eleni; Karagiannis, Chris; Darmawan, Kevion K; Ng, Ken; Hung, Andrew; Karagiannis, Tom C.
Graphical abstract: Highlights: The SARS-CoV-2 main protease (M pro ) is an important target against COVID-19. Peptidomimetic α-ketoamides represent prototypical inhibitors of the SARS-CoV-2 M pro . We confirmed the high affinity of the α-ketoamide 13b inhibitor to SARS-CoV-2 M pro MD simulations highlight α-ketoamide 13b stability in M pro compared to amoxicillin The α-ketoamide compound class could be pursued as potential antivirals against COVID-19 Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) causes an illness known as COVID-19, which has been declared a global pandemic with over 2 million confirmed cases and 137, 000 deaths in 185 countries and regions at the time of writing (16 April 2020), over a quarter of these cases being in the United States. In the absence of a vaccine, or an approved effective therapeutic, there is an intense interest in repositioning available drugs or designing small molecule antivirals. In this context, in silico modelling has proven to be an invaluable tool. An important target is the SARS-CoV-2 main protease (M pro ), involved in processing translated viral proteins. Peptidomimetic α-ketoamides represent prototypical inhibitors of M pro . A recent attempt at designing a compound with enhanced pharmacokinetic properties has resulted in the synthesis and evaluation of the α-ketoamide 13b analogue. Here, we performed molecular docking and molecular dynamics simulations to further characterize the interaction of α-ketoamide 13b with the active site of the SARS-CoV-2 M pro . We included the widely used antibiotic, amoxicillin, for comparison. Our findings indicate that α-ketoamide 13b binds more tightly (predicted GlideScore = -8.7 and -9.2 kcal/mol for protomers A and B, respectively), to the protease active site compared to amoxicillin (-5.0 and -4.8 kcal/mol). Further, molecular dynamics simulations highlight the stability of the interaction of the α-ketoamide 13b ligand with the SARS-CoV-2 M pro (ΔG = -25.2 and -22.3 kcal/mol for protomers A and B). In contrast, amoxicillin interacts unfavourably with the protease (ΔG = +32.8 kcal/mol for protomer A), with unbinding events observed in several independent simulations. Overall, our findings are consistent with those previously observed, and highlight the need to further explore the α-ketoamides as potential antivirals for this ongoing COVID-19 pandemic.